2021
DOI: 10.3390/biom11111599
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as a Valuable Biomolecule from Seafood Industry Waste in the Design of Green Food Packaging

Abstract: Chitosan is a versatile biomolecule with a broad range of applications in food and pharmaceutical products. It can be obtained by the alkaline deacetylation of chitin. This biomolecule can be extracted using conventional or green methods from seafood industry residues, e.g., shrimp shells. Chitin has limited applications because of its low solubility in organic solvents. Chitosan is soluble in acidified solutions allowing its application in the food industry. Furthermore, biological properties, such as antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 109 publications
(196 reference statements)
0
22
0
1
Order By: Relevance
“…Resveratrol, a non-flavonoid polyphenol organic compound, is a natural antitoxin that can be extracted from plants, mainly including Polygonum Cuspidate and grapes [ 4 ]. In addition, it has anti-inflammatory, anti-cancer and cardiovascular-protective effects on the human body, as well as antibacterial and antioxidant properties in organisms [ 5 , 6 , 7 ]. Therefore, there is a great arousal of interest among researchers to apply resveratrol to food packaging materials, which is advantageous for both health needs and active packaging requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol, a non-flavonoid polyphenol organic compound, is a natural antitoxin that can be extracted from plants, mainly including Polygonum Cuspidate and grapes [ 4 ]. In addition, it has anti-inflammatory, anti-cancer and cardiovascular-protective effects on the human body, as well as antibacterial and antioxidant properties in organisms [ 5 , 6 , 7 ]. Therefore, there is a great arousal of interest among researchers to apply resveratrol to food packaging materials, which is advantageous for both health needs and active packaging requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The promise of genetically engineered crops and algae is tantalizing, as previous studies have shown that genetic manipulation of organisms results in efficient secretion of biopolymeric compounds ( Moretto et al, 2020 ). Bolstered efforts for sustainable biochemical recovery are conceivable; however, eco-friendly and profitable practises to abate biowastes are needed to reroute the economy on a sustainable trajectory ( Teixeira-Costa and Andrade, 2021 ; Iqbal et al, 2022 ). Several chemical companies are experimenting with, and advocating for, new waste and recycling infrastructure strategies.…”
Section: Realising the Value Of Biowaste In The Biopolymer Industrymentioning
confidence: 99%
“…Chitosan is amongst those polymers that have been used for the design of sustainable packaging [ 9 ]. Chitosan is a linear polysaccharide derived from chitin deacetylation and is mainly obtained from crustacean shells, although it can also be extracted from fungal and insect sources [ 10 , 11 , 12 ]. Chemically, chitosan is a random copolymer composed by acetylated and deacetylated D -glucosamine units linked by β -1,4 glycosidic bonds.…”
Section: Introductionmentioning
confidence: 99%
“…They are obtained by complex formation between a hydrogen bond donor (HBD) and a quaternary ammonium salt (hydrogen bond acceptor–HBA) [ 16 ]. These mixtures present many advantages, such as being chemical and thermally stable, non-flammable, and having low volatility, melting point and toxicity, all of which makes DES a good choice for plasticizing food packaging [ 12 , 17 , 18 ]. Studies suggest that the bioaccumulation of DES in the environment is very low, log K ow values < 1.…”
Section: Introductionmentioning
confidence: 99%